"The map is not the territory". Issue 1 (26th February 2014) - Bookstein, Fred L.
Abstract Bentley et al.'s claim that their "map … captures the essence of decision making" (target article, Abstract) is deconstructed and shown to originate in a serious misunderstanding of the role of principal components and statistical graphics in the generation of pattern claims and hypotheses from profile data. Three alternative maps are offered, each with its radiation of further investigations.